APLIKASI PROBLEM BASED LEARNING DAN GROUP INVESTIGATION DALAM PEMBELAJARAN EKONOMI DI MAN MALANG I - Chiuru Umatin (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2017)
This study reported classroom participation and learning achievement after students were treated using Problem Based Learning and Group Investigation techniques. This study used classroom action research with two cycles having planning, acting, observing and reflecting as the stage in each cycle. Data source was interactions in the Class X-D of MAN Malang I. The findings of were: (1) average percentage of participatory in cycle I was 56.06% and increased 76.47% in cycle II, (2) average score of test in cycle I was 67.56% and increased into 76.88% I cycle II. In summary, Problem Based Learning and Group Investigation did increase learning achievement in economy subject of the tenth graders of MAN Malang I.